The efficacy of 5-ASA preparations in prevention of postoperative recurrence of Crohn’s disease (Retrospective assesstment) - Erkan PARLAK; Aysel ÜLKER; Canan ALKIM; Bilge TUNÇ; Ahmet TEZEL; Ülkü DAĞLI (Turkish Journal of Gastroenterology, 2019)
-